2014
DOI: 10.3168/jds.2013-6611
|View full text |Cite
|
Sign up to set email alerts
|

The effects of heat stress in Italian Holstein dairy cattle

Abstract: The data set for this study comprised 1,488,474 test-day records for milk, fat, and protein yields and fat and protein percentages from 191,012 first-, second-, and third-parity Holstein cows from 484 farms. Data were collected from 2001 through 2007 and merged with meteorological data from 35 weather stations. A linear model (M1) was used to estimate the effects of the temperature-humidity index (THI) on production traits. Least squares means from M1 were used to detect the THI thresholds for milk production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
307
9
21

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(398 citation statements)
references
References 33 publications
(47 reference statements)
36
307
9
21
Order By: Relevance
“…The previous is in agreement with those reported by Markovich (2012) in New Zealand, where milk production began to decrease at THI of 65 for H and 75 for Jerseys. Bernabucci et al (2014) also reported a reduction in milk production at THI from 65 to 76 depending of the parity of cows. There are other reports showing a range of multiple values of THI thresholds ranging from 69 to 78.2 (Bohmanova et al 2007, Bouraoui et al 2002, Dikmen and Hansen 2009, Johnson et al 1962, Ravagnolo et al 2000.…”
Section: Discussionmentioning
confidence: 90%
“…The previous is in agreement with those reported by Markovich (2012) in New Zealand, where milk production began to decrease at THI of 65 for H and 75 for Jerseys. Bernabucci et al (2014) also reported a reduction in milk production at THI from 65 to 76 depending of the parity of cows. There are other reports showing a range of multiple values of THI thresholds ranging from 69 to 78.2 (Bohmanova et al 2007, Bouraoui et al 2002, Dikmen and Hansen 2009, Johnson et al 1962, Ravagnolo et al 2000.…”
Section: Discussionmentioning
confidence: 90%
“…THI is employed as an index, which is a single value combining effects of air temperature and humidity, and to evaluate the degree of heat stress in dairy cows (Bernabucci et al, 2014). THI has been used for more than four decades to assess heat stress in dairy cows.…”
Section: Resultsmentioning
confidence: 99%
“…Dairy cows are extremely sensitive to the hot environment (Bernabucci et al, 2014), and their alterations in the endocrine status (such as insulin) under heat stress have already been reported (Rhoads et al, 2009;O'Brien et al, 2010). In fact, heat stress does not only decrease milk yield by 35%-40% (West, 2003), but also leads to health problems and metabolic disorders (Wheelock et al, 2010;Bernabucci et al, 2014). Two adipokines secreted by adipose: leptin and adiponectin, are metabolically relevant in coordinating energy homeostasis (Ailhaud, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat stress can be defined as a condition that occurs when an animal cannot adequately dissipate body heat in order to maintain thermal balance (Grover 2002, Bernabucci et al 2014. Some reports showed that Holstein milk yield decreased during HS; feed intake and management factors partly account for the decreased milk yield during heat stress (Rhoads et al 2010, Smith et al 2013, Hill and Wall 2014.…”
Section: Discussionmentioning
confidence: 99%